The major elements - Jones, J. Benton (Anderson, S.C. : On Sat One Television Productions, 1994)
The major elements of plants are covered in this video. The characteristics of these essential elements are covered in detail.
Keywords: Trace elements in plant nutrition; Plants -- Nutrition